General biology 2 - Mirabete, Glen S. (Makati City : Diwa Learning Systems, Inc., 2020)
"This textbook, the Diwa Senior High School Series: General Biology 2 (Second Edition), has been primarily designed for you to learn more concepts and relevant skills in biology. This textbook also incorporates learning activities that are indispensable for young, inquisitive 21st century learners like you. Easy-to-understand lessons and fun-filled activities are the main tools for you to successfully grasp the content of this book and have a deeper appreciation of the importance of biology in today's fast-paced world."
Includes bibliography.
English text.
Keywords: Biology